DOCUMENTARY VIDEO PRODUCTION OF “AESTHETIC DRINKS OF LOCAL BRAND IN TOWN” - Siti Hazwani Mahasim; Norsiah Abdul Hamid (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
Aesthetic drinks are currently popular among people regardless of age. The extreme demand started from the viral of these trending drinks among social media communities. Due of their appealing drinks, the bubble tea, coffee, and matcha tea cafes became popular and attracted a lot of attention when they went viral on social media.Local brands do not provide a variety of branding and not enough advertisements in the social media for people to notice them and aware of their extant. Therefore, there is a need to produce a documentary video to gain people awareness on the aesthetic drink’s brands. This article highlights the production of a documentary video titled “Aesthetic Drinks of Local Brand in Town”. The objective of this documentary video is to explore and educate people about the world of small business and marketing. It gives exposures to people on how it should be done professionally and authentically. Besides telling the audience the distinct journey of each entrepreneur, the behind-the-scenes sharing also is hoped to inspire people to build up the local business. The documentary video production contains a 2-minute teaser, 1-minute behind-the-scenes footage along with a full-fledge 15-minute documentary video. The plot of this documentary explains about the meaning of aesthetic drinks. It progresses to the next plot where it explains how these aesthetic drinks become famous in the town of Tawau, Sabah. This documentary is produced with the hope to set a clearer picture to the public about the aesthetic drinks of local brands in Tawau, so that we can better support the local business, thus help them to advance and emerge. The documentary expresses the importance of media in promoting this small business to create the awareness of local people to the product.